Global economic uncertainty: Strategic mapping for Indonesia’s pawnshop industry - Ali Sunandar; Fitri Andriyanti; Saipol Bari Abd Karim; Umi Kalsum Zolkafli @Zulkifly (Penelitian Ilmu Pengetahuan Sosial, 2026)
Background: Global economic uncertainty has become a persistent structural condition that intensifies market volatility, income instability, and financial exclusion, particularly among low-income and informally employed populations. In such contexts, pawnshops have historically functioned as countercyclical financial intermediaries by providing collateral-based liquidity when formal credit is inaccessible. Although prior studies examine pawnshops from legal, historical, Islamic finance, and consumer behavior perspectives, the literature remains fragmented and lacks an integrated strategic synthesis, especially in emerging economies such as Indonesia. This study systematically maps and synthesizes global and Indonesian literature on the pawnshop industry under conditions of global economic uncertainty and develops an integrated conceptual framework of strategic adaptation. Methods: A systematic literature review was conducted using peer-reviewed publications indexed in Scopus and Web of Science. A total of 40 selected studies were analyzed through thematic analysis. Findings: The analysis identifies five dominant themes: regulatory compliance and Sharia adaptation, digitalization and technological adoption, market demand and customer behavior, financial inclusion and economic empowerment, and historical and international perspectives. These themes converge into four strategic dimensions: risk management, customer-centric innovation, financial product diversification, and regulatory alignment. Pawnshops enhance resilience by integrating digital platforms with Sharia-compliant contracts, diversifying product portfolios, and leveraging institutional learning to manage market volatility. Conclusion: Pawnshops function as adaptive and resilient financial intermediaries whose strategic relevance increases during prolonged economic uncertainty. The integrated conceptual framework advances theoretical understanding and provides strategic guidance for policymakers and practitioners in Indonesia. Novelty/Originality of this article: This study provides the first integrated conceptual framework that systematically links global economic uncertainty with strategic adaptation mechanisms for both conventional and Sharia-compliant pawnshops in Indonesia.